2004
DOI: 10.1158/1078-0432.ccr-04-0893
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Active Mitogen-Activated Protein Kinase in Ovarian Serous Carcinomas

Abstract: Conclusions: Active MAPK is more frequently expressed in low-grade than in high-grade ovarian serous carcinoma. Active MAPK serves as a good prognostic marker in patients with high-grade serous carcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
90
4
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 126 publications
(99 citation statements)
references
References 16 publications
4
90
4
1
Order By: Relevance
“…21 We demonstrated that 92% of PSTTs expressed high levels of activated MAPK (2ϩ and 3ϩ) ( Table 1). The immunoreactivity was diffuse in PSTT and it was predominantly located in the cytoplasm.…”
Section: Expression Of Active Mapk In Normal Trophoblast and Psttsmentioning
confidence: 82%
See 2 more Smart Citations
“…21 We demonstrated that 92% of PSTTs expressed high levels of activated MAPK (2ϩ and 3ϩ) ( Table 1). The immunoreactivity was diffuse in PSTT and it was predominantly located in the cytoplasm.…”
Section: Expression Of Active Mapk In Normal Trophoblast and Psttsmentioning
confidence: 82%
“…The antibody used was a rabbit polyclonal antibody, pTEpY that specifically reacted with the active (phosphorylated) but not the unphosphorylated MAPK (Promega, Madison, WI), 21 and an anti-ERK1/2 polyclonal antibody that reacted with total MAPK (Promega). The specificity of pTEpY in immunohistochemistry was previously reported.…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Their results, along with the frequency and location of cancer-associated ERBB2 mutations, strongly suggest that this domain is critical for the regulation (enhancement) of ERBB2 activity. In the case of ovarian serous LMP tumors, activation of the RAS-MAPK pathway is evident not only through activation of mutant RAS, BRAF, and ERBB2 but also in downstream activity of (phosphorylated) ERK (75).…”
Section: Discussionmentioning
confidence: 99%
“…5,19 -21 Expression of active MAPK was more frequently observed in low-grade serous tumors than in high-grade ovarian serous carcinomas that have rare mutations in either BRAF or KRAS. 22 Moreover, BRAF and KRAS mutation status is a useful predictor of sensitivity to MEK inhibition in ovarian cancer. 11,23 Interestingly, BRAF or KRAS mutations can be detected in morphologically normal-appearing cyst epithelium that is adjacent to a serous borderline tumor but not in the cystadenomas without concurrent borderline tumors, suggesting the mutations may occur early during tumor progression of ovarian low-grade serous tumors.…”
mentioning
confidence: 99%